2022
DOI: 10.1097/iae.0000000000003519
|View full text |Cite
|
Sign up to set email alerts
|

Chandelier-Assisted Versus Standard Scleral Buckling for Primary Rhegmatogenous Retinal Detachment

Abstract: Purpose: To compare anatomical outcomes, functional outcomes, and rate of complications of standard scleral buckling (SSB) versus chandelier-assisted scleral buckling (CSB) in phakic eyes with rhegmatogenous retinal detachment.Methods: Patients were randomly assigned to either SSB or CSB. Surgical success/ failure rate, corrected distance visual acuity, surgical operating time, and rate of intraoperative and postoperative complications including epiretinal membranes by spectral domain optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…2,8,18,24 Six studies reported this complication, with incidences ranging from 5% to 48%. 2,8,10,18,24,30 Sutures at the sclerotomy site were also needed in some of the reported cases. 10,30 Authors have proposed methods to reduce the risk for vitreous prolapse, including using valved cannulas, paracentesis, or subretinal fluid drainage to lower IOP before trocar removal; inserting the trocar obliquely; or plugging the cannula during episcleral procedures as well during removal of the trocar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,8,18,24 Six studies reported this complication, with incidences ranging from 5% to 48%. 2,8,10,18,24,30 Sutures at the sclerotomy site were also needed in some of the reported cases. 10,30 Authors have proposed methods to reduce the risk for vitreous prolapse, including using valved cannulas, paracentesis, or subretinal fluid drainage to lower IOP before trocar removal; inserting the trocar obliquely; or plugging the cannula during episcleral procedures as well during removal of the trocar.…”
Section: Discussionmentioning
confidence: 99%
“…1 Scleral buckling is often performed in younger, phakic patients who have an attached posterior hyaloid because it allows for preservation of the vitreous. 2 In addition, cataractogenesis is less likely to occur with scleral buckling than with PPV, making scleral buckling more palatable for the patient. [2][3][4] However, compared with PPV, scleral buckling has disadvantages of longer operative times, a more difficult learning curve, and a higher risk for missing additional retinal breaks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As this has become more readily accessible to surgeons there has been increasing literature to support its non‐inferiority to standard indirect viewing. To date, chandelier assisted scleral buckle repair has shown primary reattachment rates ranging from 78% to 95% which is at least equally favourable to our conventional repair methods 44–46 . Unfortunately, more data are needed to see if the possible complications from disturbing the vitreous (i.e., prolapse and iatrogenic breaks) may make this technique less advantageous than it would appear.…”
Section: Scleral Bucklementioning
confidence: 99%